Does Rising Landlessness Signal Success or Failure for Vietnam's Agrarian Transition? - Ravallion, Martin; van de Walle, Dominique (2012)
In the wake of reforms to establish a free market in land-use rights, Vietnam experienced a pronounced rise in rural landlessness. To some observers this is a harmless by-product of a more efficient economy, while to others it signals the return of the pre-socialist class structure, with the rural landless at the bottom of the economic ladder. We study the issue empirically using four household surveys spanning 1993-2004. Although we find rising landlessness amongst the poor, the post-reform landlessness rate tends to be higher for the non-poor. We find no support for the claim that the process of rising landlessness has been poverty-increasing in the aggregate.